P09.13 Immune geospatial profiling and characterization of glioma microenvironment after adoptive cell therapy shows differentially expressed antigen processing and cross-presentation gene signatures. (21st September 2022) - Falceto Font, L; Francis, C; Jin, D; DiVita Dean, B; Reid, A; Long-James, K; Deleyrolle, L; Flores, C
Abstract : Background: Our group has previously shown that Adoptive Cellular Therapy (ACT) is efficacious against CNS malignancies including medulloblastoma, brain stem glioma, and glioblastoma. Here, we used GeoMx Digital Spatial profiling platform to perform in situ characterization and spatial distribution of the glioma microenvironment in tumor-bearing mice after ACT. Our goal is to elucidate the underlying cell dynamics occurring within the tumor microenvironment and determine what immune cells and gene signatures are playing a major role in overcoming treatment resistance. This method enabled us to define differences in antigen processing and cross presentation gene signatures in the ACT-treated tumors compared to untreated tumors. We also observed differences in gene expression within T cell subsets in the treated versus untreated tumors including changes in gene expression of regulatory T cell (Treg) associated genes, such as Runx1 and TGF-β. We also found a significant increase in Batf3 expression associated with therapy. Materials and Methods: To characterize the cellular dynamics behind the efficacy of this therapy, we performed in situ GeoMx Digital Spatial Profiling (DSP) and whole genome transcriptomics (RNA) of murine glioma KR-158B-luciferase tumors after adoptive cellular therapy. C57/BL6 mice were orthotopically implanted with KR158B-luciferase cells and subsequently treated with ACT. Histological slides of brain sections were sent to be stained for CD45, CD3, GFP (marks hematopoietic stem cell-derived cells) and nuclei, and processed following GeoMx DSP workflow for RNA. Gene set enrichment analysis (GSEA) was performed to determine differentially expressed gene signatures in treated vs control mice. Gene expression clustering profiles were conducted using a Principal Component Analysis (PCA), and relative gene expression differences were analyzed by unpaired t-tests. Results: Our data shows differentially expressed antigen processing and cross presentation gene signatures in the ACT-treated compared to untreated tumors by GSEA analysis. We also observed that tumors treated with ACT cluster separately from control tumors in PCA analysis and they have several differentially expressed genes. Furthermore, we found downregulation of genes associated with the suppressive properties of regulatory T cells (Runx1 and TGF-β), and upregulation of dendritic cell characteristic genes (Batf3) in ACT-treated tumors vs control. Conclusions: These findings provide insights into the immune cell dynamics and specific genes and gene signatures that are differentially expressed within the tumor microenvironment after treatment. This could help improve current adoptive cellular therapies to treat brain tumors. Disclosure Information: L. Falceto Font: None. C. Francis: None. D. Jin: None. B. DiVita Dean: None. A. Reid: None. K. Long-James: None. L. Deleyrolle: None. C. Flores: None.